SYNTHESIS AND INVESTIGATION BINUCLEAR COPPER (II) BASED ON DERIVATIVES 3-(2-PYRIDYL)-1,2,4-TRIAZOLE: UDC 541.49+546.56+547.792 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Three new binuclear Cu(II) complexes of 3-(2-pyridiyl)-1,2,4-triazole derivatives, have been synthesized and characterized by single crystal X-ray diffraction.
Keywords: complexes of copper, triazole